2a-1=3(a+1)+7a+5

Simple and best practice solution for 2a-1=3(a+1)+7a+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2a-1=3(a+1)+7a+5 equation:


Simplifying
2a + -1 = 3(a + 1) + 7a + 5

Reorder the terms:
-1 + 2a = 3(a + 1) + 7a + 5

Reorder the terms:
-1 + 2a = 3(1 + a) + 7a + 5
-1 + 2a = (1 * 3 + a * 3) + 7a + 5
-1 + 2a = (3 + 3a) + 7a + 5

Reorder the terms:
-1 + 2a = 3 + 5 + 3a + 7a

Combine like terms: 3 + 5 = 8
-1 + 2a = 8 + 3a + 7a

Combine like terms: 3a + 7a = 10a
-1 + 2a = 8 + 10a

Solving
-1 + 2a = 8 + 10a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-10a' to each side of the equation.
-1 + 2a + -10a = 8 + 10a + -10a

Combine like terms: 2a + -10a = -8a
-1 + -8a = 8 + 10a + -10a

Combine like terms: 10a + -10a = 0
-1 + -8a = 8 + 0
-1 + -8a = 8

Add '1' to each side of the equation.
-1 + 1 + -8a = 8 + 1

Combine like terms: -1 + 1 = 0
0 + -8a = 8 + 1
-8a = 8 + 1

Combine like terms: 8 + 1 = 9
-8a = 9

Divide each side by '-8'.
a = -1.125

Simplifying
a = -1.125

See similar equations:

| X+4+5x+3+4x=21 | | (y^-1/4)^1/6 | | 9-3v=0 | | 17x-36=12x+7 | | x+8=-72 | | 2(x-6)=3(x-4) | | y^(3/2)-10y | | 18=x/7 | | 66=1.5x | | -5(6y-6)-y=-3y(y-5) | | 16a^4+36a^3b-10a^2b^2= | | 5(7n-4)-3= | | -0.666+4w=-0.111 | | -7+4(1+5a)= | | 9xa+1=8a | | 2v^2(8v^2+6vb-5b^2)= | | (z^4/16)^3/4 | | (m-3)+5=16 | | 2(10x-3)-4x= | | x^2-8x+132=120 | | 5(7+6m)-10= | | 24(y-1)=-6(5+y) | | -4b+3(b+5)= | | -(v+3)-5= | | Yk+yq=k | | 4-sqrt8/sqrtx-6 | | (35x^2-32x)/(7x-5) | | 2r-(-3+6t)= | | 7x^2+5x-11=61-50x | | 3(x+3)+3=3x+7 | | 5(1-4n)-9n= | | -6m+3=4m-4 |

Equations solver categories